Coupled simulation of nonlinear ship motions and a free surface tank. (1st July 2016) - Cercos-Pita, Jose Luis; Bulian, Gabriele; Pérez-Rojas, Luis; Francescutto, Alberto
Abstract: This paper investigates the coupled nonlinear dynamics of a vessel with a free surface tank onboard. To this end, a 6-DOF ship motions simulation code is coupled with a CFD solver addressing the behaviour of the fluid in the tank. The nonlinear ship motions code is of the blended (hybrid) type, intended for the simulation of free running vessels in waves. The nonlinear CFD solver is a GPU-based 3D Weakly-Compressible Smoothed-Particle Hydrodynamic (WCSPH) solver. Numerical results are presented for the nonlinear roll motion of a vessel with and without a free surface tank in regular beam waves with different steepnesses. Nonlinear phenomena are identified and discussed. Highlights: Nonlinear coupled simulations of ship motions and sloshing in an anti-rolling tank are presented. Ship motions are simulated with a 6-DOF nonlinear blended code. Sloshing in the anti-rolling tank is simulated with a GPU-based SPH solver. Regular beam waves with different steepness are considered. Nonlinear behaviours are observed and discussed.